2012
DOI: 10.1111/jsap.12004.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in canine patients with lymphoma

Abstract: Mild proteinuria is a common finding in dogs with lymphoma. The clinical impact of the proteinuria is probably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The prevalence of proteinuria in treatment dogs tended to be higher than the control dogs and despite the range of neoplasia types represented in this study, was comparable to the prevalence of proteinuria in dogs with lymphoma or osteosarcoma previously reported (9-25%). d , 32 Group 2a dogs treated with toceranib phosphate had significantly higher SBP after the initiation of TKI treatment, which appears consistent with previous reports in both dogs b and people. [3][4][5][6][7][8][9] In a study of 20 human patients receiving sorafenib, mean SBP increased from 131 to 151 mmHg, with 75% of patients experiencing an increase of >10 mmHg and 60% increasing >20 mmHg.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of proteinuria in treatment dogs tended to be higher than the control dogs and despite the range of neoplasia types represented in this study, was comparable to the prevalence of proteinuria in dogs with lymphoma or osteosarcoma previously reported (9-25%). d , 32 Group 2a dogs treated with toceranib phosphate had significantly higher SBP after the initiation of TKI treatment, which appears consistent with previous reports in both dogs b and people. [3][4][5][6][7][8][9] In a study of 20 human patients receiving sorafenib, mean SBP increased from 131 to 151 mmHg, with 75% of patients experiencing an increase of >10 mmHg and 60% increasing >20 mmHg.…”
Section: Discussionsupporting
confidence: 89%
“…There was no statistical difference in the median UPC of control dogs and treatment dogs at baseline. The prevalence of proteinuria in treatment dogs tended to be higher than the control dogs and despite the range of neoplasia types represented in this study, was comparable to the prevalence of proteinuria in dogs with lymphoma or osteosarcoma previously reported (9–25%) , …”
Section: Discussionsupporting
confidence: 85%
“…, Di Bella et al . ). Although it would have been interesting to correlate the magnitude of persistent proteinuria with specific cancer diagnoses and even cancer stage, this was not attempted in the present study due to the large number of confounding patient variables and the limited number of cancer diagnoses other than cutaneous mast cell tumour and lymphoma.…”
Section: Discussionmentioning
confidence: 97%
“…Also, it has been demonstrated that dogs with lymphoma are more likely to be proteinuric than age‐matched controls (Di Bella et al . ), as is the case in dogs with mammary carcinoma (Crivellenti et al . ).…”
Section: Introductionmentioning
confidence: 86%
“…Neoplasia is one of several known causes of proteinuria in dogs. Potential factors contributing to the development of proteinuria in dogs with cancer include decreased renal blood flow, injury induced by products of the tumor cells, and deposition of antigen–antibody immune complexes [ 59 , 60 , 61 ]. The degree of proteinuria is generally mild, typically requiring monitoring rather than immediate intervention [ 59 ].…”
Section: Discussionmentioning
confidence: 99%